Response of geomagnetic variations and 30 MHz riometer absorption, at Indian Antarctic station MAITRI, to conditions of “zero” and “high” solar wind - Rajaram, G.; Dhar, Ajay; Kumar, S. (2001)
Variations in the 30 MHz cosmic radio noise signal, and in the Y, X, Z fluxgate magnetometer traces recorded at the Indian Antarctic station MAITRI (geom. 62°.8 S, 52°.8 E, L = 4.8) are compared for the “zero solar wind” day of 11 May 1999 (ΣKp = 20), the very Quiet day 22 Dec 1999 (ΣKp = 10), and the very Disturbed day 18 May 1999 (ΣKp = 310). Interplanetary magnetic field and solar wind parameters from the WIND satellite for these days are also examined, in order to understand what factors cause Maitri to change from a location influenced by Sq currents, to one influenced by Auroral electrojet currents. It is observed that it is not only negative Bz and high solar wind velocity which play a role in causing pronounced magnetic disturbance at this just-sub-auroral location but also high ion density and high ion dynamic pressure in the solar wind. The observations reflect on the changes which occur in the size of the geomagnetosphere and in the size of the auroral oval as a consequences of changes in the Interplanetary medium.